Respuesta :
Step-by-step explanation:
Multiply everything in the parenthesis.
24. (2xy)( -4x²) + (6x)(6x²y)
---> -8x³y + 36x³y
= 28x³y
25. (2ab²)(4a²b³) - (10a³b)(6b⁴)
---> 8a³b^5 - 60a³b^5
= -52a³b^5
Sorry, i cant turn the 5 into an exponent on my phone lol. but i hope this helps.
Question :
❖ Use the product rule to simplify the following monomials.
Answers :
24. (2xy)( -4x²) + (6x)(6x²y)
[tex] \tt = (2xy)( -4x²) + (6x)(6x²y) \\ \tt = ( - 8 {x}^{3} y) + 36 {x}^{3} y \\ \tt = 28 {x}^{3} y \: \: \: \: \: \: \\ \\ \\ [/tex]
25. (2ab²)(4a²b³) - (10a³b)(6b⁴)
[tex] \tt = (2ab²)(4a²b³) - (10a³b)(6b⁴) \\ \tt = 8 {a3}^{2} {b}^{5 } - 60 {a}^{3} {b}^{5 } \: \: \: \: \: \: \\ \tt = - 52 {a}^{3} {b}^{5 } \: \: \: \\ \\ \\ [/tex]